The ontological and functional status of robots: How firm our representations are?. (September 2015) - Gaudiello, Ilaria; Lefort, Sébastien; Zibetti, Elisabetta
Highlights: We investigate teenagers' robot representation (ontological and functional status). We observe whether such representation changes with acquaintance to robots. The ontological categorization of robots becomes more nuanced. The functional categorization of robot stays more strictly defined. No third ontological category seems to emerge. Abstract: Robot representation is a moving target : according to our previous experience and to the context of use, we constantly reinvent what we consider to be 'robot'. In this paper we investigate teenagers' robot representation, with special concerns to educational robots. By robot representation we mean its (i) ontological and (ii) functional status. Particularly, we seek to understand whether teenagers' judgment about (i) and (ii) changes when they become acquainted with robots. To this aim, we carried out an experimental study with pre- and post-questionnaires with 79 participants during a robotic event: the RoboParty®. Results show that building and programming a robot fosters a more nuanced judgment about robots' belonging to the living and non-living categories but, on the other side, a more definite judgment about the educative functions that a robot may serve. Thus, at this stage of technology development in contemporary society, robots seem to share something with living entities and some other things with non-living ones. Just like living entities, robots hold an ontological status that admits degrees; similarly to non-living entities, robots need to have a precise function in order for users to have a meaningful interaction with them. Moreover, contrary to our prediction and to current literature, no new category – beyond those of living and non-living ones-seems to emerge in teenagers' ontology. However, cues pointing out that dealing with robots might have an impact on traditional boundaries of common-sense ontology are discussed.